Effect of Solution pH and Concentration of Dewandaru Fruit Extract as a Natural Dye on Optical Characteristics and Performance of Dye-Sensitized Solar Cells - Dadi Rusdiana; Eka Cahya Prima; Muhammad Nurul Ikhsan; Andhy Setiawan; Endi Suhendi; Arip Nurahman; Semuel Unwakoly; Arramel Arramel (International Journal of Renewable Energy Development, 2026)
Given growing global energy demand and the need for sustainable solutions, solar energy is a promising alternative. Dye-Sensitized Solar Cells (DSSC) represent a cost-effective photovoltaic technology, and natural dyes as sensitizers have significant potential to enhance their efficiency. This study explores the use of natural dye from Dewandaru fruit (Eugenia uniflora) in DSSCs by varying pH levels and concentrations. Natural dyes offer an environmentally friendly and sustainable alternative compared to synthetic dyes, which are often expensive and not eco-friendly. In this research, Dewandaru fruit extract was used to sensitize TiO2 photoanodes, and the effects of varying pH (1.00, 1.66, 2.27, and 3.00) and dye concentrations (2.5, 5.0, 7.5, and 10%) on optical properties and performance were analyzed. UV-Vis spectroscopy, FTIR, cyclic voltammetry, and J-V measurements assessed absorbance, energy levels, and efficiency. Optical characterization results showed that changes in pH and concentration can affect the dye’s absorbance and energy band gap. The optimal DSSC performance for the dye was found at pH 3.00, yielding a Voc of 0.425 V, Jsc of 0.053 mA/cm², fill factor of 68.7%, and efficiency of 0.1548%. The best dye concentration was 10%, achieving a Voc of 0.45 V, Jsc of 0.105 mA/cm², fill factor of 69.0%, and efficiency of 0.322%. The statistical analysis indicates that pH substantially and positively influences DSSC efficiency and band gap energy. Moreover, dye concentration significantly affects DSSC efficiency, light harvesting efficiency, Jsc, and fill factor, with the most substantial impacts observed on efficiency and Jsc. However, concentration appears to have less effect on dye absorbance, band gap energy, and the HOMO/LUMO values. The study indicates that Dewandaru fruit extract has potential as a natural dye for DSSCs, with varying performance based on pH and concentration.